Penerapan Teknologi Pengelolaan Modal Kerja Sebagai Upaya Meningkatkan Pendapatan Toko Bahan Bangunan Di Bantul - Linawati; Sutrischastini, Ary; Sofiati (DHARMA BAKTI, 2022)
The existence of a building shop in an area has an important role in serving and meeting theneeds of the local community for building houses, renovating, and other building activities.Likewise, building shops in Bantul Regency have a no different role. The problem is inmanaging the building shop business, most of the financial reports, especially workingcapital, have not been managed properly considering that this business is generally ahereditary business, so that its management is done traditionally and manually. The purposethis article is to report the results of Community Service through increasing self-capacity bypresenting the Building Shop Working Capital Management Training in Bantul Regency. Torepresent building shops in the Bantul Regency area, this research used 2 building shops assamples. There are three stages of the training method used, (1) providing material, (2)practice and mentoring, and (3) monitoring and evaluation. The target and outcome to beachieved from this program is to produce entrepreneurs and company managers who haveknowledge and understanding of financial management, especially working capitalmanagement, so that they can make financial administration and financial documentsproperly which in turn can increase income optimally.